Genetic variation in resistance to leaf fungus indirectly affects spider density - Slinn, Heather (2017)
Many host-plants exhibit genetic variation in resistance to pathogens; however, little is known about the extent to which genetic variation in pathogen resistance influences other members of the host-plant community, especially arthropods at higher trophic levels. We addressed this knowledge gap by using a common garden experiment to examine whether genotypes of Populus trichocarpa varied in resistance to a leaf-blistering pathogen, Taphrina sp., and in the density of web-building spiders, the dominant group of predatory arthropods. In addition, we examined whether variation in spider density was explained by variation in the density and size of leaf blisters caused by Taphrina. We found that P. trichocarpa genotypes exhibited strong differences in their resistance to Taphrina and that P. trichocarpa genotypes that were more susceptible to Taphrina supported more web-building spiders, the dominant group of predatory arthropods. We suspect that this result is caused by blisters increasing the availability of suitable habitat for predators, and not due to variation in herbivores because including herbivore density as a covariate did not affect our models. Our study highlights a novel pathway by which genetic variation in pathogen resistance may affect higher trophic levels in arthropod communities.